Using the “Analysis of the Mind” method to teach the module “Human health and addictions”. - L.K. Romanova (International Consortium of Education and Culture Research Studies, 2019)
In the learning process, a student learns a lesson under the direct guidance of a teacher, using the content, methods, tools and forms of education, acquiring knowledge, skills and abilities. As you know, there is an increasing interest in the use of interactive methods, innovative technologies, pedagogical and information technologies in the educational process. One of the reasons is that traditional education has so far taught students to acquire only the latest knowledge, while modern technology teaches them to independently explore and analyze the knowledge they have acquired, and even to draw conclusions. In addition, interactive methods allow students to master the learning materials on the basis of joint discussions. Consequently, they will have the opportunity to study the material in pairs, in small groups, and in large groups on complex issues.